The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1063/1.4883860
|View full text |Cite
|
Sign up to set email alerts
|

Local control of magnetic damping in ferromagnetic/non-magnetic bilayers by interfacial intermixing induced by focused ion-beam irradiation

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 36 publications
(44 reference statements)
3
22
0
Order By: Relevance
“…2(a) and 2(c) with three characteristic regions can be understood by considering several intrinsic and extrinsic effects occurring at the interface of the FM and NM layers. It is known that d-d hybridization, spin-pumping, and two-magnon scattering are the effective factors for damping enhancement in FM/NM thin films [3,4,11,13,17,21,23]. The experimental results are in agreement with a recent theoretical study [3] where damping increases with increasing Pt capping layer thickness up to a broad peak followed by a decrease to constant value with further increases in thickness.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…2(a) and 2(c) with three characteristic regions can be understood by considering several intrinsic and extrinsic effects occurring at the interface of the FM and NM layers. It is known that d-d hybridization, spin-pumping, and two-magnon scattering are the effective factors for damping enhancement in FM/NM thin films [3,4,11,13,17,21,23]. The experimental results are in agreement with a recent theoretical study [3] where damping increases with increasing Pt capping layer thickness up to a broad peak followed by a decrease to constant value with further increases in thickness.…”
Section: Discussionsupporting
confidence: 81%
“…This can occur when the symmetry of the system is disturbed by structural defects like film roughness and intermixing [1,3,21] and will enhance the effective damping of the magnetization precession. Increased intermixing will also enhance the effective spin-mixing conductance [8,21,22], and modifying the interface will affect all of the mechanisms mentioned above [4,23]. It is therefore of great interest to study the evolution of precessional magnetic damping in FM/NM bilayers as the interface develops as a function of the NM thickness.…”
Section: Introductionmentioning
confidence: 99%
“…is observed that a remains almost constant over a range of frequency between 8.5 to 15 GHz, from which it is inferred that in this sample, extrinsic phenomena, 24 such as two magnon scattering, do not contribute to the effective damping. In order to investigate the effect of spin torque on damping, a dc current was passed through the stack.…”
mentioning
confidence: 75%
“…37 It has been observed previously that interfacial intermixing at the NiFe/ Au interface increases with increasing ion dose and here this may contribute to the increased DW pinning, although the topological roughness is not significantly enhanced. Also, the magnetic damping has also been shown to increase with ion-beam irradiation 43 and this may have an effect on the dynamic interaction of a propagating DW with the pinning region in our experimental measurements. This dynamic behavior was not included in the quasi-static micromagnetic analysis performed here with an artificially high damping parameter of a ¼ 0.5.…”
Section: Resultsmentioning
confidence: 63%